Differential transcriptome and metabolite profile with variable fluoride tolerance and altered genomic template stability in the identification of four fluoride-tolerant or fluoride-sensitive rice cultivars - Ankur Singh; Aryadeep Roychoudhury (Plant Stress, 2023)
Fluoride toxicity is the most commonly experienced challenge to rice plants due to irrigation with fluoride-polluted groundwater. In the present study, four hydroponically grown rice cultivars (Badshahbhog, Swarna, Sukumar and Shatabdi) were screened for fluoride tolerance on the basis of physiological and molecular parameters. Rice cultivars were maintained at 37 °C under 16/8 h light/dark photoperiodic cycle with 700 μmol photons m−2 s−1 intensity and relative humidity (50 %) in a plant growth chamber for 20 days. Treatment with NaF (50 mg L−1) caused considerable fluoride accumulation in Shatabdi which hindered its growth and triggered the formation of H2O2 and enhanced lipoxygenase and protease activity that eventually led to higher malondialdehyde formation and electrolyte leakage from the cells. This was accompanied with degradation of photosynthetic pigments (chlorophyll a, b, total chlorophyll, xanthophyll and carotenes) and inhibition in Hill activity. Higher formation of osmolytes (proline, amino acids and glycine betaine) and activity of enzymatic antioxidants (SOD, CAT, APX and GPX) reversed the effect of fluoride toxicity in Badshahbhog, concomitant with proper maintenance of the expression of gene concerned with photosynthetic mechanism (PsbA, PsbY, PsaH, PetC, PetH, Rbcs, Rca and rsp9) which preserved the photosynthetic machinery, providing sufficient energy to the seedlings to overcome the stressed conditions. RAPD profiling and GTS also established the superiority of Badshahbhog over the three cultivars, making it an efficient fluoride-tolerant variety.